Financial Literacy And Income On Interests In Saving - Yunengsih, Tiara Wirda; Yanti, Novi; Erniwati, Erniwati; A, Abdul Rahim; Marseli, Anisa (Al-Hijrah: Journal of Islamic Economics And Banking, 2023)
This study aims to determine the effect of financial literacy and income on the interest in saving at PT. BPR Tri Capital Investama (TCI) West Sumatra. The population in this study was the North Pariaman District Community with a total sample of 100 respondents, where the research data was obtained through a questionnaire which was then processed using an instrument test, data analysis techniques using the classical assumption test, multiple linear regression analysis, hypothesis testing and determination of the R2 coefficient. The results of the t test study show that (1) financial literacy has no significant effect on the intention to save with a t value of 1.937 < t table 1.98 with a significance value of 0.056 > 0.05, and (2) income has a significant effect on the intention to save by the calculated t value is 6.697 > 1.98 with a significance value of 0.000 < 0.05. The results of the f test show that (3) financial literacy and income simultaneously (together) affect the intention to save the t-count value of 6.697 > 1.98 with a significance value of 0.000 <0.05. The determination of 40.1% while the remaining 59.9% is influenced by variables other than the independent variables in the study. It is hoped that the people of North Pariaman Subdistrict will be able to increase awareness of the importance of financial literacy, and also be more proactive in studying existing financial aspects to maintain and manage finances in the future.